IMPLEMENTASI PROGRAM DAKWAH SEBAGAI SARANA PENANAMAN NILAI PENDIDIKAN AGAMA ISLAM UNTUK PENINGKATAN AKHLAK DAN PEAKTEK IBADAH SISWA DI SMP 11 MARET KEC. AMBARAWA KAB. PRINGSEWU - Muhtarom, Muhtarom; Purwanti, Eri; Umurohmi, Ulfah (JURNAL MANAJEMEN PENDIDIKAN ISLAM AL-IDARAH, 2016)
The role of the planting program of Islamic education in public and private schools is still very minimal. Planting of Islamic education as there are only in environment of school that religion based. But in junior high school 11Maret Sumber Agung, whose status as private schools were able to bring the exclusive through the study religious invitation program. This Program able to increase attitude or morality of the students as well as the activities of worship student in school environment.The purpose of this study was to determine the role of religious invitation program on the attitudes or moral and religious practices of students in the school. This study uses a quantitative descriptive approach. The results of this study showed an increase in students' attitudes and moral and religious practices in school as many as 25% from 52.5% to be 77.5%.